The Dowry Value of a Set of Prayer Equipment: An Anthropological Analysis of Islamic Law - Moh. Ainul Yakin Putra; Khadeejeh Alrawashdeh; Abdul Haq Syawqi (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2025)
The purpose of this study is to determine the status of dowry in the form of prayer equipment from the perspective of MadÅ¼ahib Al-Arba'ah in Nyalabu Daya Village, Pamekasan District. The research method used is qualitative with interview techniques to understand the existing phenomenon in depth. This study shows that the community tends to regard a set of prayer equipment as a symbol of worship and cannot be used as the main dowry because it cannot be converted or traded at a later date, while the Shafi'i and Hambali schools of thought allow dowries in the form of benefits or services.